Habitat use and spatial distribution patterns of endangered pheasants on the southern slopes of the HimalayasFigshare - Kai Zhao; Ning Wang; Jiliang Xu; Shan Tian; Yanyun Zhang (Global Ecology and Conservation)
The southern slopes of the Himalayas, with their significant altitudinal gradients and diverse climates and habitats, harbour exceptional biodiversity and serve as crucial habitats for endangered pheasant species in Asia. However, increasing human disturbances pose severe threats to local ecosystems. Understanding the distribution patterns of endangered pheasants and their responses to environmental changes is vital for their conservation. This study utilised infrared camera traps combined with the Joint Species Distribution Model and the MaxEnt model to analyse the spatial distribution patterns of Satyr Tragopan (Tragopan satyra) in the southern Himalayas and predict its future responses to climate change. The results indicate that Satyr Tragopan is primarily distributed in riverine forests at altitudes between 2700 m and 3600 m. Its occupancy probability was significantly influenced by altitude, human activity disturbances, and forest cover proportion. Species co-occurrence patterns revealed a significant positive correlation between Satyr Tragopan and Hill Partridge, Mainland Serow, and Chinese Goral, suggesting similar habitat requirements or mutualistic relationships. MaxEnt model predictions indicated that, under future climate scenarios, the suitable habitat for Satyr Tragopan is projected to increase, particularly expanding westwards into Nepal under the SSP245 scenario. However, owing to its limited dispersal ability and poor habitat connectivity, the survival of Satyr Tragopan remains threatened. This study emphasizes the importance of enhancing habitat connectivity, establishing new protected areas, and reducing habitat fragmentation, thus providing a scientific basis for the long-term conservation of pheasants on the southern slopes of the Himalayas.